1994
DOI: 10.1111/j.1744-618x.1994.tb00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Expert Validation and Differentiation of the Nursing Diagnoses Anxiety and Fear

Abstract: In this study, the author (a) identifies and validates critical and supportive characteristics of the nursing diagnosis anxiety, and (b) differentiates the defining characteristics of the nursing diagnosis anxiety from the nursing diagnosis fear. The sample consisted of 233 nurses with a master's degree in psychiatric‐mental health nursing or medical‐surgical nursing. The study design followed the nurse validation model of Gordon and Sweeney (1979) as expanded by Fehring (1986, 1987). Following concept analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
9

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 10 publications
1
31
0
9
Order By: Relevance
“…The literature review showed that many researchers have worked to refine some DCs for the nursing diagnoses proposed by NANDA‐I (Adams et al., 1997; Whitley, 1994); they have suggested the inclusion of new characteristics supported by the literature and confirmed by validation studies of nursing diagnoses (Levin & Krainovich‐Miller, 1999; Taylor‐Loughran et al., 1989). Among these papers, there are some related to the anxiety diagnosis (Fadden, Fehring, & Kenkel‐Rossi, 1987; Wake, Fehring, & Fadden, 1991; Young, Polzin, Todd, & Simuncak, 2002); others are on both diagnoses (Adams et al., 1997; Levin & Krainovich‐Miller, 1999; Whitley, 1994, 1997), and there are also papers that suggest a possible association between both diagnoses (Adams et al., 1997; Whitley, 1997). There are no published reports by authors who have developed consensual validation and clinical validation of the diagnoses and their DCs or who have discussed the correlation between them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review showed that many researchers have worked to refine some DCs for the nursing diagnoses proposed by NANDA‐I (Adams et al., 1997; Whitley, 1994); they have suggested the inclusion of new characteristics supported by the literature and confirmed by validation studies of nursing diagnoses (Levin & Krainovich‐Miller, 1999; Taylor‐Loughran et al., 1989). Among these papers, there are some related to the anxiety diagnosis (Fadden, Fehring, & Kenkel‐Rossi, 1987; Wake, Fehring, & Fadden, 1991; Young, Polzin, Todd, & Simuncak, 2002); others are on both diagnoses (Adams et al., 1997; Levin & Krainovich‐Miller, 1999; Whitley, 1994, 1997), and there are also papers that suggest a possible association between both diagnoses (Adams et al., 1997; Whitley, 1997). There are no published reports by authors who have developed consensual validation and clinical validation of the diagnoses and their DCs or who have discussed the correlation between them.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors tried to categorize the DCs presented for these diagnoses in the NANDA‐I 1999/2000 version into critical characteristics and noncritical characteristics in an attempt to organize the suggested list (Adams et al., 1997; Levin & Krainovich‐Miller, 1999). Whitley (1994) and Levin, Lunney, and Krainovich‐Miller (2004) proposed a categorization of the DCs for anxiety, such as affective, physiological, behavioral, and cognitive characteristics; subjective and objective characteristics were proposed for fear. These studies were regarded as significant in refining both diagnoses and led to a change in their definitions and the list of DCs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, fear denotes an unpleasant feeling of threat or danger with a clearly definable object (Burke, 1981). Anxiety, when it is defined as fear of the unknown, can hamper postoperative recovery (Whitley, 1994). Fear and anxiety are normal and useful emotions that can motivate learning and positive behaviour, but they can also lead to maladaptive responses and it is essential to assist clients to deal positively with the situation causing the fear (Whitley, 1992; Salmon, 1993).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Metzer and Hiltunen (1987) identified six responses as critical cues of anxiety: anxiousness, apprehension, increased tension, worry, fear of specific consequences, and distress. Four of these six defining characteristics—anxiousness, apprehension, increased tension, and worry—also were identified in Whitley's (1994) anxiety study. Fadden, Fehring, and Kenkel‐Rossi (1987) found no characteristic of anxiety on the current list of defining characteristics that reached a defining characteristic ratio of 0.50 or greater.…”
Section: Discussionmentioning
confidence: 98%
“…Anxiety is a concept frequently included in nursing and other healthcare literature, and is a global health problem with a large scope of etiologies presenting with confusing comorbidities, the sequelae of which may result in functional impairments and may place heavy demands upon healthcare services. Anxiety is a health issue that occurs in the top 10 nursing diagnostic categories used by practicing nurses in different settings (Levin, Krainovich, Bahrenburg, & Mitchell, 1989; Whitley, 1994). The North American Nursing Diagnosis Association (NANDA) established the nursing diagnosis of Anxiety in 1973 in its first National Conference in St. Louis, Missouri (Moorhead & Brighton, 2001), and is now recognized as a leader in nursing classification systems.…”
mentioning
confidence: 99%